UPAYA PENINGKATAN PENGETAHUAN DAN PELATIHAN PENGOLAHAN KERIPIK DAN TEH KULIT BUAH PISANG MAS SEBAGAI PANGAN KAYA ANTIOKSIDAN DI KECAMATAN TAMANSARI KOTA TASIKMALAYA - Rani Rubiyanti; Imat Rochimat; Nooryza Martihandini (Edukasi Masyarakat Sehat Sejahtera (EMaSS) : Jurnal Pengabdian kepada Masyarakat, 2023)
Tamansari Village is one of the villages in Tasikmalaya City that occupies the highest case of Covid as of 2020. In 2020, knowledge has been increased by counseling on how to use vitamin C properly and correctly as well as processed herbs to increase immunity. As a target area, the knowledge transfer process was continued with training on the processing of banana mas peels in the form of chips and tea which had previously been researched on antioxidant activity in 2021. The target to be achieved is that cadres / communities can maintain immunity with healthy processed food and rich in antioxidants and be creative and can make processed products made from banana peels to be used as chips and tea as an opportunity for entrepreneurship so that it can increase family income and be able to analyze the feasibility of entrepreneurship in making snacks. The method of implementing community service activities is the provision of training and counseling on the process of making processed chips and banana mas peel tea. The implementation of community service activities will be carried out in 2022 with 4 meetings (exploration, implementation of phase I, implementation of phase II and evaluation). The results and outputs of service are the increase in public knowledge shown by an increase in post-test value by 80% and the creation of processed products of chips and banana peel tea shown by the existence of a video as an evaluation material for posyandu cadres in processing banana peels.